(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article is dedicated to the problems of national and world mythology. The article content is determined by the terms «myth» and «mythology». It also deals with the values of the basic mythological ideas and images contrasted to the oldest human feelings. Over the millennia, myths were the most important part of the spiritual culture. The people’s perceptions of themselves and the world, space and time, reality and existence were also reflected here. It is impossible to understand the spiritual world of ancient human without resorting to the myths. The examples of national and world mythology were presented and considered in the article.